The role of green innovation in promoting sustainable economic development in Gweru, Zimbabwe - Wilson Mabhanda (Journal of Sustainable Tourism and Entrepreneurship, 2024)
Purpose: In developing countries, such as Zimbabwe, the nexus between green innovation and sustainable economic development has not been thoroughly investigated. To fill this gap, this study examined the role of green innovation in promoting sustainable economic development in Gweru and Zimbabwe. Research Methodology:  Interpretivist philosophy underpinned qualitative data collection through a multi-case study method and thematic analysis approaches. Fifteen purposively and conveniently sampled participants participated in face-to-face interviews and focus-group discussions. Results: The study’s findings revealed that green innovation was a precursor to sustainable economic development through the reduction of carbon emissions and climate change, supply of clean energy, and increasing agricultural production, all of which enable employment generation and improved standards of living. Limitations: This study was limited to only green solar entrepreneurs in Gweru City, and other cities were not covered. The study was qualitative; hence, the results cannot be generalized to other cities in the country. Contributions: This study contributes by expanding the body of knowledge on the green innovation agenda for Small to Medium Enterprises in the solar power systems of Zimbabwe; in addition, the use of protection policies can stimulate friendly environmental businesses in all sectors of the economy.